2011
DOI: 10.1021/jf203012a
|View full text |Cite
|
Sign up to set email alerts
|

Role for p53 in Selenium-Induced Senescence

Abstract: The tumor suppressor p53 and the ataxia-telangiectasia mutated (ATM) kinase play important roles in the senescence response to oncogene activation and DNA damage. It was previously shown that selenium-containing compounds can activate an ATM-dependent senescence response in MRC-5 normal fibroblasts. Here, the shRNA knockdown approach and other DNA damage assays are employed to test the hypothesis that p53 plays a role in selenium-induced senescence. In MRC-5 cells treated with methylseleninic acid (MSeA, 0-10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…On the other hand, in MRC-5 fibroblasts treated with methylselenic acid (up to 10 μM), it was revealed that Se compounds can also induce senescence mediated by a DNA damage response and increased amounts of SA-β-Gal were found [207]. Furthermore, sodium selenite treatment (20 µM) attenuates the interaction of the heat shock protein Hsp90 with the IκB-Kinase (IKK) in tumor cells – thus promoting inactivation of the NF-κB pathway and inhibition of autophagy via downregulation of Beclin 1 expression, inducing a cell signaling switch from autophagy to apoptosis [208].…”
Section: The Role Of Trace Elements and Micronutrients In Agingmentioning
confidence: 99%
“…On the other hand, in MRC-5 fibroblasts treated with methylselenic acid (up to 10 μM), it was revealed that Se compounds can also induce senescence mediated by a DNA damage response and increased amounts of SA-β-Gal were found [207]. Furthermore, sodium selenite treatment (20 µM) attenuates the interaction of the heat shock protein Hsp90 with the IκB-Kinase (IKK) in tumor cells – thus promoting inactivation of the NF-κB pathway and inhibition of autophagy via downregulation of Beclin 1 expression, inducing a cell signaling switch from autophagy to apoptosis [208].…”
Section: The Role Of Trace Elements and Micronutrients In Agingmentioning
confidence: 99%
“…In the case of selenium, it has been shown that supranutritional doses can reduce the risk of lung, prostate and colorectal cancers [28]. The possible mechanism for selenium’s chemopreventive properties is diverse, from inducing cellular senescence [29,30,31] to activating cell cycle arrest [27,32] or by intracellularly generation of ROS [33,34,35,36,37], among others. However, it cannot be said unequivocally that selenium supranutrition can prevent cancer under all circumstances [38,39].…”
Section: Nutrition and Cancermentioning
confidence: 99%
“…Importantly, these cellular and molecular changes were not observed in the prostate of wild type littermates treated with MSeA. Since P53 signaling is likely to be intact in HG-PIN compared to advanced PCa, the selective super-activation of P53-mediated senescence by MSeA in these mouse studies and the results of the aforementioned cell culture studies in normal fibroblasts indicating senescence induction by MSeA (83) (84), suggest a new mechanistic paradigm of cancer chemoprevention by strengthening a barrier to cancer progression through induction of irreversible senescence with additional suppression of oncogenic androgen receptor and AKT signaling. A comparison of the efficacy of MSeA and MSeC with SeMet remains to be determined regarding the specificity of effects via the p53-p21-senescence pathway.…”
Section: Efficacy Studies Of Next-gen Se To Inhibit Prostate and Omentioning
confidence: 85%
“…In addition, the ataxia telangiectasia mutated (ATM) DNA damage response protein was rapidly activated by MSeA and its kinase activity was required for the induced senescence response. Subsequently depletion of p53 was demonstrated to attenuate senescence, disrupt the MSeA-induced cell cycle arrest, and increased genome instability (84). Pretreatment with KU55933, an ATM kinase inhibitor, or NU7026, an inhibitor of DNA-dependent protein kinase, desensitized MSeA cytotoxicity in normal fibroblasts but not in fibroblasts with knocked down p53.…”
Section: Next-gen Se Compounds In Cancer Chemoprevention: Methylsementioning
confidence: 99%